2015
DOI: 10.1089/zeb.2014.1010
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Exposure of Zebrafish Embryos to Arecoline Leads to Retarded Growth, Motor Impairment, and Somite Muscle Fiber Changes

Abstract: The areca nut-chewing habit is common in Southeast Asia, India, and Taiwan, and arecoline is the most abundant and potent component in the areca nut. The effects of arecoline on birth defects have been explored in many species, including chicken, mice, and zebrafish. The effects of arecoline on embryos after long-term exposure are well established; however, the effects of short-term embryo exposure to arecoline are not understood. Using zebrafish, we study the effects of short-term exposure of arecoline on emb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
21
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 45 publications
2
21
0
1
Order By: Relevance
“…The betel nut metabolite, arecoline, may lead to muscular mitochondria dysfunction and affect either the arrangement or the integrity of muscle fibres or a reduction of locomotor activity 22. With regard to the cardiovascular system, current betel nut chewing would increase HR, irrespective of the frequency of usage, due to central sympathetic response, but the effect on BP may vary by the peripheral cholinergic effect, resulting in a fall of the diastolic component 4.…”
Section: Discussionmentioning
confidence: 99%
“…The betel nut metabolite, arecoline, may lead to muscular mitochondria dysfunction and affect either the arrangement or the integrity of muscle fibres or a reduction of locomotor activity 22. With regard to the cardiovascular system, current betel nut chewing would increase HR, irrespective of the frequency of usage, due to central sympathetic response, but the effect on BP may vary by the peripheral cholinergic effect, resulting in a fall of the diastolic component 4.…”
Section: Discussionmentioning
confidence: 99%
“…Betel nut chewing becomes popular since they elicit a psychoactive effect in humans [ 2 ]. In addition, betel nut is also listed as the most addictive substance in the world along with tobacco, alcohol, and caffeine [ 3 ]. The psychoactive effect in betel nut is associated with arecoline (methyl 1,2,5,6-tetrahydro-1-methyl nicotinate) [ 4 ], which is the most abundant nicotinic acid-based alkaloid in betel nut [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, arecoline alkaloid is able to promote peristalsis and glandular secretion by acting on both muscarinic and nicotinic receptors [ 1 , 7 ]. International Agency for Research on Cancer (IARC) has found evidence demonstrating that chewing betel nut could cause oral cancer in humans [ 3 ]. However, arecoline can be used for medicinal purposes such as anti-helminthic, mental illness drugs, digestive agents, as well as psychosomatic medicine [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Peng et al (2015) correlacionaram alterações em fibras musculares de embriões de zebrafish, expostos a Arecolina, com a diminuição no crescimento das larvas. Além disso, estudos in vitro e in vivo realizados porSavi et al (2014) Gráficos representativos de corte transversal.…”
unclassified